HUBUNGAN TINGKAT PENGETAHUAN MAKANAN BERGIZI DAN PENDIDIKAN IBU DENGAN SIKAP DALAM UPAYA PENCEGAHAN STUNTING PADA BALITA DI RW.011 KELURAHAN PEJATEN TIMUR - Anggraini, Nourmayansa Vidya; Suratmini, Dwi; Tri Wahyudi, Chandra; Suci Rahmanti, Septia (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
The mother's level of knowledge and education regarding stunting prevention plays an important role in stunting prevention. In previous research, research had not been carried out on these two things, namely the level of knowledge and education of the mother and attitudes towards preventing stunting. This study aims to analyze the relationship between the level of maternal knowledge about nutritious food and maternal education and their attitudes towards preventing stunting in toddlers. The method used is non-experimental quantitative research with a correlational descriptive design, using a cross-sectional study approach. A total of 148 samples were selected using random sampling techniques, and data was obtained through filling out questionnaires whose validity and reliability were tested. The sample criteria in this study were mothers who had children under five (0-59 months), lived in sub-district Y and were willing to be research respondents. The questionnaire used was a questionnaire related to knowledge and education and the mother's attitude in preventing stunting. The results of analysis using Spearman correlation showed that there was a significant relationship between mothers' knowledge about nutritious food and their attitudes towards preventing stunting (r = 0.404, p < 0.001). In addition, there was a stronger relationship between mothers' education level and their attitudes towards stunting prevention (r = 0.569, p < 0.001). It is hoped that mothers can increase their knowledge about nutrition and stunting prevention by participating in nutrition education programs and utilizing resources to provide nutritious food at affordable costs. The recommendation for future research is to conduct research related to other factors that influence mothers' attitudes in preventing stunting.